Peran Teknologi Digital dalam Meningkatkan Manajemen Pelayanan Rumah Sakit di Tengah Perubahan Kebijakan Kesehatan - Victor ED Palapessy; Rini Susanti; Suriyani Suriyani; Rika Irawan (SEHATI: Jurnal Kesehatan, 2026)
This study aims to explore the impact of digital technology on hospital management in the context of changing healthcare policies. The main focus of the research is to understand how the implementation of digital technology can enhance operational efficiency and patient satisfaction within the dynamic healthcare policy environment. The research design used is quantitative with a survey approach, where data was collected through questionnaires from 50 respondents working in hospitals that have adopted digital technology. Data analysis was conducted using descriptive statistics and multiple linear regression to examine the relationship between digital technology variables and hospital management. The main findings of this study indicate that digital technology improves operational efficiency and patient satisfaction, but is also confronted with challenges such as inadequate staff training and data security issues. Additionally, supportive healthcare policies accelerate the adoption of digital technology in hospitals. This study contributes to hospital management literature by highlighting the important role of digital technology in improving healthcare services. The practical implication of these findings is the importance of supporting policies and adequate staff training. Future research is recommended to adopt a longitudinal design and expand the sample to monitor the long-term impact of digital technology in hospitals